Investigating the impact of ICT investments on human development - Bankole, Felix Olubisi (Department of Information Systems, 2015)
In the last two decades, the worldwide information and communication technology (ICT) market has been growing at a rapid rate. This has led to the global net increase in ICT usage and investments. International organizations, ICT vendors, policy makers have been trying to determine if such huge investments are worthwhile. However, the result regarding this issue is inconclusive, for this research area is fraught with complexity and existing empirical study is limited. Investigating the impact of ICT investments on human development requires appropriate methods that can provide a deeper understanding and which are based on IS perspective theory. Of particular importance are different aspects of ICT investments and the components of human development. For example, ICT investments consist of four aspects namely hardware, software, internal spending and telecommunication investments while human development components are GOP, literacy rates and life expectancy rates. If these variables are not modelled correctly, their effect on each other can be either under- or overestimated and the appropriate level of impact is therefore required.